Investigation on Properties and Pyrolysis Performance of Natural Rubber/Sugarcane Bagasse Biocomposites - Saowapark, Thanunya; Jaturapiree, Adisak; Sukrat, Kanjarat; Wattananit, Witoon; Chaichana, Ekrachan (Asian Journal of Chemistry, 2025)
Sugarcane bagasse has been frequently used as a filler in natural rubber biocomposites to enhance mechanical properties. In addition, the presence of bagasse filler also enhances other properties of natural rubber biocomposites including thermal properties and chemical properties, which could influence the pyrolysis recycling process when recycled. Therefore, the effect of bagasse filler on the pyrolysis recycling process was investigated along with the mechanical and thermal properties. A pristine natural rubber (NR) and bagasse-natural rubber biocomposites (NR/BG) with various amounts of bagasse (5, 10 and 15 phr) were prepared. The pyrolysis processes were conducted at 400 ºC for all samples, and the obtained products were analyzed. It was found that most of the mechanical properties of the rubber samples including tensile strength, modulus and tear strength increased with increasing the amount of bagasse. In addition, thermal stability of NR/BG were better than that of NR. When pyrolyzing the rubber samples, it was observed that all the pyrolyzed liquids have the nearly heating values, between 43.1-44.2 MJ/kg suggesting no significant change in fuel property. However, the chemical composition of the obtained liquids considerably varied, especially limonene which was found higher in the liquids from NR/BG (61.9-73.4 wt.%) than that from NR (31.65 wt.%). The presence of BG inside NR/BG biocomposites changes chemical compositions of the biocomposites, especially Zn which possess the catalytic ability to convert the primarily-generated limonene into other products, and also provided low hydrogen-to-carbon source which reduced the conversion of limonene.